jdaai 2023
DOI: 10.46632/jdaai/2/2/1
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Survey on Eye Care Services in Bengaluru

Abstract: The eye care industry in India is growing at a rapid pace, and Bengaluru is one of the fastest- growing cities in the country with a significant demand for quality eyecare services. The purpose of this research paper is to provide a comprehensive market study of the eyecare services market in Bengaluru, including an overview of the market size, growth potential, competition, and prospects. The study reveals that the market is growing at a significant rate due to the rising prevalence of eye disorders and disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Studies have found that visual problems are higher among those less educated and who live in rural areas [ 5 ]. Numerous studies have looked into the ECU pattern and the risk variables that are linked to it [ 6 13-18 undefined undefined undefined undefined undefined ]. This article attempts to evaluate the pattern of ECU among adults in Malawi, concentrating on related demographic parameters, given that ECU varies with context.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that visual problems are higher among those less educated and who live in rural areas [ 5 ]. Numerous studies have looked into the ECU pattern and the risk variables that are linked to it [ 6 13-18 undefined undefined undefined undefined undefined ]. This article attempts to evaluate the pattern of ECU among adults in Malawi, concentrating on related demographic parameters, given that ECU varies with context.…”
Section: Introductionmentioning
confidence: 99%